SAM Functionalized ZnO Nanowires for Selective Acetone Detection: Optimized Surface Specific Interaction Using APTMS and GLYMO Monolayers. (14th July 2020) - Singh, Mandeep; Kaur, Navpreet; Drera, Giovanni; Casotto, Andrea; Sangaletti, Luigi; Comini, Elisabetta
Abstract: In modern days, self‐assembled monolayer (SAM) functionalized surfaces represent an interesting tool for the development of ultrasensitive and selective sensing platforms for the detection of chemical substances such as biomolecules and gases. The ability of SAM to generate different functional groups on a single surface such as zinc oxide (ZnO) can be used to immobilize biomolecules and detect different analytes such as gases, proteins, etc. Herein, SAM functionalized ZnO NW‐based sensors are developed for acetone exhaled breath analysis. ZnO NWs are synthesized using a vapor–liquid–solid mechanism and their functionalization is done with two different SAMs, i.e., (3‐aminopropyl)trimethoxysilane (APTMS) and 3‐glycidoxypropyltrimethoxysilane (GLYMO). The enhancement in the electron depletion layer resistance (and also width) due to the capturing of electrons from the ZnO NWs surface by APTMS and GLYMO molecules is found to be the major reason in their superior sensing performances. The amine (–NH2 ) groups of APTMS monolayer enhance the sensors selectivity toward acetone due to their reactions with acetone molecules, which produce imine in addition to water molecules. Moreover, after the functionalization with APTMS SAMs, the detection limits of the sensors are improved from 6 to 0.5 ppm, which makes these devices potential candidates for acetone exhaled breath analysis. Abstract : Vapor–liquid–solid grown zinc oxide nanowire sensors functionalized with (3‐aminopropyl)trimethoxysilane monolayer exhibit excellent selectivity and a detection limit of 0.5 ppm toward acetone due to enhanced surface specific interactions between acetone and amine groups and hence demonstrate a potential for acetone exhaled breath analysis.